The importance of the family in the school context: a case study in a public school in the State of Piauí during the pandemic (Research, Society and Development, 2022)
The purpose of this article was to show the relevance of the family in the school environment, mainly, in the present day that had a great foundation for the process and learning to happen efficiently, over time the family with the main founder of the children's education, has becoming increasingly important in the school context, contributing directly to the education of students. The theme arose from the need to facilitate this teaching and learning process, we realized that this process requires an active participation of the family within the school, to have satisfactory teaching. The work was based on field research and literature. When analyzing some theorists such as Silva and Araújo, Santos and Serrano, Krauss, Orth and Robins, among others, who have dedicated themselves to the present theme, it only reinforced how important the family-school relationship is, in construction of individuals in the intellectual, emotional and social aspects. It is concluded that the relationship between school and family is very important for the learning of students, the family needs to participate actively in school meetings, and to have this follow-up in the educational process of their children, given the research carried out, parents are fundamental to satisfactory and quality teaching.